2009
DOI: 10.1007/s11684-009-0059-9
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic sigmoid vaginoplasty in women with Mayer-Rokitansky-Kuster-Hauser syndrome

Abstract: The feasibility and clinical therapeutic effects of laparoscopic sigmoid vaginoplasty in women with Mayer-Rokitansky-Kuster-Hauser syndrome (MRKHs) were explored. The records of 11 MRKHs patients who underwent laparoscopic sigmoid vaginoplasty from 2003 to 2005 were reviewed, and long-term results were evaluated by follow-up. The mean operating time was 234 min (range, 130-300 min), the mean hospital stay was 9.4 days (range, 7-15 days), and the mean hemoglobin drop was 1.91 g/dL (range, 1.6-3.2 g/dL). A funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Several authors reported a laparoscopic technique for isolating a segment of sigmoid colon to be used for vaginal construction as a minimally invasive procedure. It could be one of the methods of choice, but only in the hands of experienced and skilled surgeons [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Several authors reported a laparoscopic technique for isolating a segment of sigmoid colon to be used for vaginal construction as a minimally invasive procedure. It could be one of the methods of choice, but only in the hands of experienced and skilled surgeons [17,18].…”
Section: Discussionmentioning
confidence: 99%